2008
DOI: 10.2174/1874471010801030177
|View full text |Cite
|
Sign up to set email alerts
|

Astatine Radiopharmaceuticals: Prospects and Problems

Abstract: For the treatment of minimum residual diseases such micrometastases and residual tumor margins that remain after debulking of the primary tumor, targeted radiotherapy using radiopharmaceuticals tagged with α-particle-emitting radionuclides is very attractive. In addition to the their short range in tissue, which helps minimize harmful effects on adjacent normal tissues, α-particles, being high LET radiation, have several radiobiological advantages. The heavy halogen, astatine-211 is one of the prominent α-part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 128 publications
0
69
0
Order By: Relevance
“…melanoma), and intracavitary tumors such as neoplastic meningitis [9,12]. Therapeutic application of 211 At has been impeded by a number of issues including lack of availability of this nuclide, identification of appropriate carrier molecules whose pharmacokinetics are compatible with its 7.2 h half-life, and the synthesis of stable prosthetic groups that enable labeling biomolecules with high yield and stability [11,31]. Despite the high potential of 211 At for targeted radiotherapy, only a few methods have been utilized for attaching 211 At to targeting vectors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…melanoma), and intracavitary tumors such as neoplastic meningitis [9,12]. Therapeutic application of 211 At has been impeded by a number of issues including lack of availability of this nuclide, identification of appropriate carrier molecules whose pharmacokinetics are compatible with its 7.2 h half-life, and the synthesis of stable prosthetic groups that enable labeling biomolecules with high yield and stability [11,31]. Despite the high potential of 211 At for targeted radiotherapy, only a few methods have been utilized for attaching 211 At to targeting vectors.…”
Section: Resultsmentioning
confidence: 99%
“…Radium-223, as the radium chloride salt, was approved by the FDA as the first α-therapeutic (Xofigo ® ) for treatment of symptomatic metastatic castration-resistant prostate cancer [9,10]. For more complex targeting approaches, the 7.2-h radiohalogen 211 At has many promising properties including a half-life long enough for performing multi-step labeling, quality control and clinical application without the problematic characteristic of having relatively long lived α-particle emitting daughters [1113]. Each 211 At decay is accompanied by emission of α particles with an average energy of 6.4 MeV, corresponding to a mean tissue range of 65 µm [14].…”
Section: Introductionmentioning
confidence: 99%
“…211 At emits K x-rays with its a-decay to 211 Po, allowing for sample counting and scintigraphic imaging of 211 At in vivo (14). Astatine belongs to the halogen family, and radiolabeling can be performed by adapting radioiodination chemistry (15). Tin precursors and prosthetic groups have been used to label small molecules, peptides, or antibodies (15).…”
Section: Atmentioning
confidence: 99%
“…Astatine belongs to the halogen family, and radiolabeling can be performed by adapting radioiodination chemistry (15). Tin precursors and prosthetic groups have been used to label small molecules, peptides, or antibodies (15). The carbon-astatine bond is relatively weak, and the release of free astatine can result in undesired toxicity (16).…”
Section: Atmentioning
confidence: 99%
“…The current approach for labelling biomolecules with 211 At rests on covalent attachment to a carbon atom. 8 Unfortunately, a significant number of studies have shown that astatinated radiopharmaceuticals can be stable to in vitro conditions, but generally more unstable in vivo. 9,11 Nevertheless, clinical studies are in progress in United State and in Sweden.…”
Section: Radioimmunotherapy (Rit) Is a Developing And Promising Technmentioning
confidence: 99%